Model Pendidikan Transformatif dalam Rekonstruksi Pembelajaran Pendidikan Islam di Era Digital - Sifaul Khusnah; Annisa Nuril Faradisa; Moh Padil; Ni’matuz Zuhroh (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines the transformative education model in the reconstruction of Islamic education learning in the digital era. The main issue in this study is the continued dominance of conventional teaching methods, which are less cap able of adapting to the development of digital technology and changes in student characteristics. This situation necessitates a renewal of learning approaches so that Islamic education remains relevant to the needs of the digital generation. This study aims to analyze the concept of transformative education and to explain the urgency of reconstructing Islamic education learning in the digital era. The method used is library research with a qualitative approach through the analysis of various books and relevant scholarly journal articles.The results of the study indicate that the transformative education model emphasizes critical reflection, active student participation, and changes in perspectives in understanding social and religious realities. The reconstruction of Islamic education learning also needs to be carried out through the utilization of digital technology, the development of dialogue and critical discussion methods, and the integration of interactive learning media to make the learning process more contextual and engaging. Furthermore, transformative education encourages students to develop critical thinking skills, digital literacy, and awareness of Islamic values in dealing with various information in the digital era. Thus, the implementation of the transformative education model can serve as a relevant approach in building Islamic education learning that is adaptive, participatory, and contextual. Keywords: Transformative Education, Learning Reconstruction, Islamic Education, Digital Era.